Merekonstruksi Konsep I‘Tikāf melalui Tafsir Ilmiah: Menjembatani Spiritualitas dan Rasionalitas Al-Qur’an - Muhamad Daffa Ghazial Fawwaz; Jahrotu Soimah; Yeni Andriyani; Rohmat hidayatullah; Andi Rosa (Jurnal Budi Pekerti Agama Islam, 2025)
This study explores the reconstruction of the concept of I‘tikāf through the scientific interpretation (tafsir ilmi) of the Qur’an, aiming to bridge the gap between spirituality and rationality. The research employs a qualitative approach using library research methods to analyze Qur’anic verses related to I‘tikāf and various classical and contemporary tafsir works. The primary sources include the Qur’an and interpretations from scholars such as M. Quraish Shihab, al-Maraghi, and Ibn ‘Ashur. The study finds that I‘tikāf, when viewed through the lens of scientific exegesis, offers not only a spiritual retreat but also a space for reflection, intellectual development, and personal transformation. This integrated understanding enhances the relevance of Qur’anic teachings in the context of modern life, emphasizing that spirituality and reason are not mutually exclusive but complementary in the Islamic worldview.